Regulatory interactions between CD45RBhigh and CD45RBlow CD4+ T cells are important for the balance between protective and pathogenic cell-mediated immunity. - Powrie, F; Correa-Oliveira, R; Mauze, S; Coffman, R (1994)
BALB/c mice infected with the intracellular protozoan Leishmania major mount a T helper cell 2 (Th2) response that fails to control growth of the parasite and results in the development of visceral leishmaniasis. Separation of CD4+ T cells into CD45RBhigh and CD45RBlow subsets showed that the L. major-specific Th2 cells were contained within the CD45RBlow population as these cells produced high levels of antigen-specific interleukin 4 (IL-4) in vitro and transferred a nonhealing response to L. major-infected C.B-17 scid mice. In contrast, the CD45RBhighCD4+ population contained L. major-reactive cells that produced interferon gamma (IFN-gamma) in vitro and transferred a healing Th1 response to L. major-infected C.B-17 scid mice. Transfer of the Th1 response by the CD45RBhigh population was inhibited by the CD45RBlow population by a mechanism that was dependent on IL-4. These data indicate that L. major-specific Th1 cells do develop in BALB/c mice, but their functional expression is actively inhibited by production of IL-4 by Th2 cells. In this response, the suppressed Th1 cells can be phenotypically distinguished from the suppressive Th2 cells by the level of expression of CD45RB. Although the CD45RBhigh population mediated a protective response to L. major, C.B-17 scid mice restored with this population developed a severe inflammatory response in the colon that was independent of L. major infection, and was prevented by cotransfer of the CD45RBlow population. The colitis appeared to be due to a dysregulated Th1 response as anti-IFN-gamma, but not anti-IL-4, prevented it. Taken together, the data show that the CD4+ T cell population identified by high level expression of the CD45RB antigen contains cells that mediate both protective and pathogenic Th1 responses and that the reciprocal CD45RBlow population can suppress both of these responses. Whether suppression of cell-mediated immunity is beneficial or not depends on the nature of the stimulus, being deleterious during L. major infection but crucial for control of potentially pathogenic inflammatory responses developing in the gut.